2007
DOI: 10.1108/03074350710753753
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of stock market development in the Middle‐Eastern and North African region

Abstract: PurposeThe purpose of this study is to investigate the role of stock markets in economic growth and to shed some light on the macroeconomic determinants which must have an important influence on stock markets development.Design/methodology/approachThe empirical study is conducted using an unbalanced panel data from 12 Middle Eastern and North African (MENA) region countries. Econometric issues are based on estimation of some fixed and random effects specifications.FindingsIt is found that saving rate, financia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
106
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 29 publications
16
106
0
3
Order By: Relevance
“…They showed that liquid stock markets had a significant and subsequent impact on economic growth. Naceur et al (2007) found that saving, financial institutions, stock market liquidity and inflation are important determinants of stock market development. The empirical study covered the time period 1979-1999.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that liquid stock markets had a significant and subsequent impact on economic growth. Naceur et al (2007) found that saving, financial institutions, stock market liquidity and inflation are important determinants of stock market development. The empirical study covered the time period 1979-1999.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whenever economic conditions of a country allow a high rate of saving i.e., people save part of their income in addition to paying daily expenses, we can say investment in that country will be strengthened. On one hand, it is possible to guess that investment is one of the important factors determining stock exchange capital since investment rate depends on saving rate (Naceur et al, 2007). On the other hand, stock exchange could not be developed without the existence of an efficient system of financial intermediaries including underwriters, dealers, etc.…”
Section: Factors Affecting Stock Exchange Developmentmentioning
confidence: 99%
“…External non-economic factors affecting the stock exchange development are classified as political, legal, social, cultural, and technological factors (Osulian, 2006;Black, 2001;Boubakri and Olfa, 2007;Torre et al, 2006). These internal and external studies conclude that national income, saving rate, investment rate, financial intermediary development, liquidity of stock exchange, liberalization of stock exchange, privatization, macroeconomic instability, tax rate, interest rate, inflation rate and currency rate are among the most important, effective macroeconomic variables on stock exchange development (Osulian, 2006;Black, 2001;Boubakri and Olfa, 2007;Naceur et al, 2007;Torre et al, 2006). In this research, four variables including national income, investment rate, financial intermediary development, and macroeconomic instability have been selected according to Garcia and Liu (1999).…”
Section: Factors Affecting Stock Exchange Developmentmentioning
confidence: 99%
See 2 more Smart Citations